Wireless communications systems theory and applications /c Abid Yahya, Farid Ghani, R.Badlishah Ahmad, Othman Sidek - Abid Yahya; Farid Ghani; R.Badlishah Ahmad; Othman Sidek (Unit Penerbitan, Universiti Malaysia Perlis, 2011)
This book explores the research and development of encryption codes and spread spectrum systems